Evaluation of User Acceptance of Enterprise Resource Planning System at Material Resource Planning Division of PT. Xacti Indonesia - Rahmadan, Fakhri; Mursityo, Yusi Tyroni; Wardani, Niken Hendrakusma (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2021)
The purpose of this evaluation is to evaluate user acceptance of the Glovia ERP system, whichever embedded in PC to assist operator staffs to record material stocks. The research methodology used in this study is the UTAUT model adjusted for the research problem's conditions. The issue happens because the Staff feel more comfortable with the old procedure and think it has supported their performance well. The respondents, as the sample in this study, are the staff operator from the MRP division. Data analysis is done using Partial Least Squares—the result of the research state that the Performance Expectancy variable has a significant effect on the Behavioral Intention variable. On the contrary, the other variables do not significantly affect the Behavioral Intention variable. The behavioral Intention variable has an R square value of 0.352 percent, which states that four independent variables can explain 35.2% of the Behavioral Intention variable. From the test results, it is suggested that the MRP division of PT can use the recommendations. Xacti Indonesia, as a consideration that can be used to improve the system currently applied.